Yokohama, California - Mori, Toshio, 1910-1980 (Classics of Asian American literature., 2015)
Yokohama, California, originally released in 1949, is the first published collection of short stories by a Japanese American. Set in a fictional community, these linked stories are alive with the people, gossip, humor, and legends of Japanese America in the 1930s and 1940s.